Access to housing in the neoliberal era: a new comparativist analysis of the neoliberalisation of access to housing in Santiago and London. Issue 3 (3rd July 2019) - Beswick, Joe; Imilan, Walter; Olivera, Patricia
Abstract: The housing crisis in cities across the globe has been shaped by an architecture of neoliberal housing policy. However, to bring myriad qualitatively and nationally disparate modes of housing privatisation, restriction, individualisation and marketisation under the umbrella of a single, monolithic 'neoliberalism' risks limiting explanatory power, ignoring national particularity and privileging theory over 'actually existing neoliberalism'. Therefore, this paper attempts a cosmopolitan understanding of these processes across the North/South dichotomy, comparing the trajectories of two cities seen as archetypal examples of housing neoliberalisation: Santiago and London. Drawing on Latin American and Global North literatures, we analyse the socio-spatial and political-institutional effects emerging from neoliberal transformations of access to housing. By exploring mutations in: the role of the state; the origin/purpose of funding/financing; the class composition of policy beneficiaries; the geography of public housing; and, housing tenure, the paper produces a rich comparison of two significantly different housing systems. Written in the spirit of 'new comparativism', the paper contributes to the ongoing decentring of Western-dominated theories of neoliberalism. Two importantly different city-trajectories emerge, and these particularities enable us to add depth to our understanding of the current housing crises, while at the same time drawing cross-border comparisons and conclusions, and cosmopolitanising our theories of neoliberalisation.